2015
DOI: 10.1186/s40064-015-1354-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophilic pseudomonas in antarctic freshwater lake at stornes peninsula, larsemann hills over east Antarctica

Abstract: The Larsemann Hills is an ice-free area of approximately 50 km2, located halfway between the Vestfold Hills and the Amery Ice Shelf on the south-eastern coast of Prydz Bay, Princess Elizabeth Land, East Antarctica (69º30′S, 76º19′58″E). The ice-free area consists of two major peninsulas (Stornes and Broknes), four minor peninsulas, and approximately 130 islands. The Larsemann Hills area contains more than 150 lakes at different Islands and Peninsulas. Nine lake water samples were collected in a gamma steriliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Studies using a culture-dependent approach showed that Pseudomonas spp. are (sub)dominant among cultivated bacteria in the Arctic and Antarctic (Chauhan et al 2015, Romaniuk et al 2018), which is in line with our data. Pseudomonads well tolerate various environmental conditions due to their high metabolic versatility (Ozen & Ussery 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Studies using a culture-dependent approach showed that Pseudomonas spp. are (sub)dominant among cultivated bacteria in the Arctic and Antarctic (Chauhan et al 2015, Romaniuk et al 2018), which is in line with our data. Pseudomonads well tolerate various environmental conditions due to their high metabolic versatility (Ozen & Ussery 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the purchased frozen food was distributed by a single supplier for all farms. Pseudomonadaceae can survive at freezing temperature (Lu et al, 2011; Chauhan et al, 2015). Therefore, our initial hypothesis was that P. aeruginosa could be selected compared to other freezing-sensitive gut microbiota species and replicate in defrosted food.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas spp. were also found in permanently cold, polar regions, including Arctic and Antarctic marine waters, glaciers and soil [6,7,8,9]. Studies applying a culture-dependent approach revealed that Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%